Implementasi Standard Operating Procedures (SOP) dalam Meningkatkan Pelayanan Umrah Pada PT Semesta Alam Mandiri (Tiraz Travel) Jakarta Selatan - nurmaliah nurmaliah (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2020)
This research discusses the SOP of Umrah departure and the implementation of SOP in improving Umrah services at PT. Semesta Alam Mandiri (Tiraz Travel). SOP is a very important thing to use as a guideline and reference for company activities.With the SOP can minimize the deviations that occur in a Hajj and Umrah Travel and the company will be more effective and more controlled, so that it has an impact on the services to be provided. The results of this study show that the implementation of SOP in improving Umrah services at PT. Semesta Alam Mandiri (Tiraz Travel) South Jakarta, has been going quite well, but there are still some services that are not contained in the SOP only run based on company habits and culture. However, not causing anything fatal still has a positive impact. Keywords: Keywords: Standard Operating Procedures (SOP), Service, Umrah